2014
DOI: 10.1038/bjc.2014.310
|View full text |Cite
|
Sign up to set email alerts
|

The role of patient, tumour and system factors in socioeconomic inequalities in lung cancer treatment: population-based study

Abstract: Background:Reducing socioeconomic inequalities in lung cancer treatment may reduce survival inequalities. However, the reasons for treatment variation are unclear.Methods:Northern and Yorkshire cancer registry, Hospital Episode Statistics and lung cancer audit data sets were linked. Logistic regression was used to explore the role of stage, histology, performance status and comorbidity in socioeconomic inequalities in lung cancer treatment, for 28 733 lung cancer patients diagnosed in 2006–2010, and in a subgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
(44 reference statements)
1
18
0
Order By: Relevance
“…As the prognosis of lung cancer differs greatly among resected and nonresected patients, it is important to distinguish between these groups. A few population-based studies have considered lung cancer patients overall, regardless of resection status, but focusing on trends in incidence or prognoses associated with different treatments [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…As the prognosis of lung cancer differs greatly among resected and nonresected patients, it is important to distinguish between these groups. A few population-based studies have considered lung cancer patients overall, regardless of resection status, but focusing on trends in incidence or prognoses associated with different treatments [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic inequalities in receipt of treatment for lung cancer have been demonstrated in a systematic review and meta-analysis9 and in previous analyses of the dataset used here 10. It has been suggested that socioeconomic inequalities in receipt of treatment may at least partially contribute to socioeconomic inequalities in cancer survival,11 although there is little definitive evidence to support this.…”
Section: Introductionmentioning
confidence: 65%
“…The results from both analyses led to the same findings, which were consistent with results previously published. First, the stage at diagnosis was the strongest predictor of receiving surgery 10. The patient’s PS and the indication of a PET-CT scan performed32 were also strongly associated with surgery.…”
Section: Discussionmentioning
confidence: 97%